2020
DOI: 10.3390/cells9071688
|View full text |Cite
|
Sign up to set email alerts
|

Human and Rodent Skeletal Muscles Express Angiotensin II Type 1 Receptors

Abstract: Abundant evidence reveals that activation of the renin-angiotensin system promotes skeletal muscle atrophy in several conditions including congestive heart failure, chronic kidney disease, and prolonged mechanical ventilation. However, controversy exists about whether circulating angiotensin II (AngII) promotes skeletal muscle atrophy by direct or indirect effects; the centerpiece of this debate is the issue of whether skeletal muscle fibers express AngII type 1 receptors (AT1Rs). While some investigators asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Recently, our group has confirmed that AT1Rs exist on the sarcolemma of skeletal muscle fibers 24 and we also discovered that activation of the AT1R is required to promote VIDD. Specifically, pharmacological blockade of the AT1R attenuated MV-induced oxidative stress, contractile dysfunction, and muscle fiber atrophy in the diaphragm 25,26 .…”
Section: Accepted Articlementioning
confidence: 64%
See 3 more Smart Citations
“…Recently, our group has confirmed that AT1Rs exist on the sarcolemma of skeletal muscle fibers 24 and we also discovered that activation of the AT1R is required to promote VIDD. Specifically, pharmacological blockade of the AT1R attenuated MV-induced oxidative stress, contractile dysfunction, and muscle fiber atrophy in the diaphragm 25,26 .…”
Section: Accepted Articlementioning
confidence: 64%
“…Importantly, treatment of animals with Ang1-7 has been shown to protect locomotor muscles against atrophy due to prolonged inactivity or high circulating levels of AngII. 22,23 Recently, our group has confirmed that AT1Rs exist on the sarcolemma of skeletal muscle fibers 24 and we also discovered that activation of the AT1R is required to promote VIDD. Specifically, pharmacological blockade of the AT1R attenuated MV-induced oxidative stress, contractile dysfunction, and muscle fiber atrophy in the diaphragm.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…To eliminate the risk of contamination of other tissue types that may be abundant in RAS proteins (i.e., vascular tissue), individual muscle fibers (~3 ​mm in length) were isolated from bundles of costal diaphragm, soleus, and plantaris muscles as previously described by Deminice et al. 34 Briefly, bundles of muscle fibers were placed in a relax solution (in mM: 100 KCl, 20 imidazole, 4 ATP, 2 EGTA, and 7 MgCl 2 ; pH adjusted to 7.0 using KOH) on ice where ~80 individual muscle fibers were carefully isolated under a stereomicroscope and placed into Eppendorf tubes prepared for Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%